Т. 3; Сборник аннотированных фольклорных и бытовых текстов обско-енисейского языкового ареала - Фильченко А. Ю. Андрей Юрьевич; Потанина О. С. Ольга Сергеевна; Тоноян М. Н.; Курганская Ю. В. Юлия Васильевна; Крюкова Е. А. Елена Александровна; Байдак А. В. Александра Владимировна; Максимова Н. П. Наталья Петровна; Федотова Н. Л. Надежда Леонидовна; Ковылин С. В. Сергей Васильевич; Лемская В. М. Валерия Михайловна; Токмашев Д. М. Денис Михайлович; Ким А. А. Антонина Александровна (Изд-во Вайар, 2013)
Заглавие с экрана